SHIFTING BUSINESS STRATEGY OF INTERNATIONAL STANDARD HOSPITAL IN METAVERSE ERA - Yurika Santika Dewi; Gede Sri Darma (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2022)
As the most impacted sector by the pandemic situation, healthcare services should be prepared to encounter the Metaverse era. Hospitals should start thinking strategies to be taken, especially for International Standard Hospital. The aim of the research is to determine and evaluate the effectiveness of shifting business strategy conducted by BIMC Siloam Nusa Dua Bali Hospital in encountering metaverse era. Qualitative and quantitative data is used in this research by using techniques of collecting data through interviews, observation, and documentation. Research informants as many as 8 people, the Chief Executive Officer, top management representatives, and operational representatives. For triangulation informants were represented by the Chief of Management, the Chief of Operating, and two patients. The used of analysis technique in this research is qualitative analysis. The result research indicate the occurrence of shifting business strategy initially with (1) main market is from foreign tourist turning onto domestic tourist, local residents and expats, (2) the existence of digitalization service innovations, and (3) the emergence of new product, Crisalix Virtual Aesthetics, and Bariatric Surgery.